2004
DOI: 10.1002/gps.1040
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and depressive symptoms in Chinese elderly

Abstract: Both obese elderly men and women in Hong Kong were less likely to suffer from depressive symptoms than those of normal weight. The results support the 'jolly fat' hypothesis previously restricted to men, and extend the hypothesis to female elderly. Chinese traditional culture and positive values towards obesity may be protective against depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
53
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 29 publications
13
53
2
Order By: Relevance
“…In contrast to the several studies in Western countries showing a positive relationship between obesity and depression (Luppino et al, 2010; Sachs-Ericsson et al, 2007), an inverse relationship between BMI and depressive symptoms was found in our study. This finding is consistent with the results from two Asian countries with Korea, namely Japan and China (Kuriyama et al, 2006; Li et al, 2004), where a higher weight has also been regarded as a sign of wealth and health in the past (Li et al, 2004). Finally ADL, IADL limitations were also associated with depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the several studies in Western countries showing a positive relationship between obesity and depression (Luppino et al, 2010; Sachs-Ericsson et al, 2007), an inverse relationship between BMI and depressive symptoms was found in our study. This finding is consistent with the results from two Asian countries with Korea, namely Japan and China (Kuriyama et al, 2006; Li et al, 2004), where a higher weight has also been regarded as a sign of wealth and health in the past (Li et al, 2004). Finally ADL, IADL limitations were also associated with depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Obese elderly were less likely to suffer from depressive symptoms than those of normal weight; this was confirmed in a study from Hong Kong in China [61]. Our results also supported obesity had better HRQL in the mental component summary.…”
Section: Strengths and Limitationssupporting
confidence: 85%
“…Crisp and colleagues [16, 17] even coined the term “jolly fat” to capture the idea of the association between being overweight and being happy when they found that an overweight, middle-aged suburban and rural population reported low levels of anxiety and depression. There was further support for the “jolly fat” hypothesis in other population-based studies, which found that higher body mass index (BMI) was inversely associated with depression scores in an older population [18, 19]. However, it has been pointed out that overweight adults might be less likely to reveal negative emotions to others due to social desirability bias [16] or cultural values [19], or that appetite might play a moderating role on the relationship between obesity and depression [18].…”
Section: Introductionsupporting
confidence: 64%
“…There was further support for the “jolly fat” hypothesis in other population-based studies, which found that higher body mass index (BMI) was inversely associated with depression scores in an older population [18, 19]. However, it has been pointed out that overweight adults might be less likely to reveal negative emotions to others due to social desirability bias [16] or cultural values [19], or that appetite might play a moderating role on the relationship between obesity and depression [18]. …”
Section: Introductionsupporting
confidence: 64%